The 'refugee crisis' and its transformative impact on EU-Western Balkans relations. Issue 6 (26th April 2022) - Webb, Jonathan
ABSTRACT: The EU's relations with the countries of the Western Balkans are traditionally characterised by a set of stable relations and power dynamics. While the impact of the 'migration crisis' on EU migration policy has been examined, comparatively little attention has been placed on the social construction of the crisis and its impact on EU external relations. Specifically, there remains a lack of scholarship ascertaining the relationship between the framing of the crisis as a security threat, and EU policy change towards non-EU countries in Southeast Europe. To address these gaps, this article explores to what extent the securitisation of the crisis led to policy changes and the consequence of these changes on EU relations with the countries of Macedonia and Serbia. It demonstrates how in exchange for their cooperation with the EU to address the crisis, the Western Balkans governments extracted significant political concessions from the EU. Changes in policy and practice by the EU further enabled Macedonia and Serbia to justify concessions from the EU. This is argued to represent a continued shift in the relationship between the EU and Western Balkans countries, all be it one driven by the spiralling securitisation of the crisis.